Maximizing expectancy violation and exposure outcomes in patients with PTSD - Marike J. Kooistra; Maartje Schoorl; Danielle A. C. Oprel; Willem van der Does; Rianne A. de Kleine (European Journal of Psychotraumatology)
Background: It has been proposed that maximizing expectancy violation enhances the efficacy of exposure therapy. The clinical utility of expectancy violation remains unclear and it has not yet been studied in PTSD.Objective: We aimed to test whether explicitly focusing on expectancy violation leads to superior exposure outcomes.Method: Adult treatment-seeking patients with PTSD (N = 60) were randomly assigned to one 90-minute exposure session focusing on either expectancy violation or a control condition without an expectancy focus. Assessments occurred before the session and one week later, measuring changes in fear responses during a script-driven imagery task, and PTSD symptoms.Results: Using multilevel analyses, we found no between-condition differences. On average, fear responses to the imagery and PTSD symptoms decreased over time. The expectancy violation condition exhibited a greater decrease in threat appraisal, which appeared to mediate symptom reduction.Conclusions: We found no evidence that explicitly focusing on expectancy violation led to superior immediate effects. However, it may lead to more changes in expectancies which could affect symptom improvement over an extended period. Further research is needed to determine whether emphasizing expectancy violation in exposure therapy for PTSD is advantageous.